2018
DOI: 10.1021/acs.energyfuels.8b01731
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Ketones in a Petroleum Source Rock

Abstract: A comprehensive investigation of oil composition is important for the petroleum industry as well as the understanding of natural science. Ketones commonly exist in petroleum; however, as a result of the low concentrations and limitations inherent in the analytical technique, the molecular composition of these compounds is rarely studied. In this study, ketones in a source rock were characterized by gas chromatography–mass spectrometry, Fourier transform ion cyclotron resonance mass spectrometry, and Orbitrap m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Wang et al 186 investigated ketones in a source rock by the derivatization with the Girard T reagent and found that the chemical derivatization followed by (+) ESI MS analysis is suitable for the analysis of ketones, but it has discrimination on high DBE species (DBE ≥ 9). Direct analysis with (+) APPI MS showed comparable ionization efficiency throughout the DBE range and could distinguish aliphatic ketones from aromatic ketones according to different ionization pathways.…”
Section: Approaches and Applications Formentioning
confidence: 99%
“…Wang et al 186 investigated ketones in a source rock by the derivatization with the Girard T reagent and found that the chemical derivatization followed by (+) ESI MS analysis is suitable for the analysis of ketones, but it has discrimination on high DBE species (DBE ≥ 9). Direct analysis with (+) APPI MS showed comparable ionization efficiency throughout the DBE range and could distinguish aliphatic ketones from aromatic ketones according to different ionization pathways.…”
Section: Approaches and Applications Formentioning
confidence: 99%
“…Vanadium compounds; 296 Non-polar aromatic compounds; 297 thiols; [298][299][300] Sulfides; 301,302 N-, S-, and O-containing species; 129,198,205,207,212,214,221,224,236,244, Porphyrins; [348][349][350][351][352] Molecular structure of Asphaltenes; 185,216,353,354 naphthenic acids; 284,285,[355][356][357][358][359][360] petroleum sulfonates; [361][362][363][364] acidic compounds; 213,215,216,323,362,[365][366][367][368][369][370][371]…”
Section: Esi (Electrospray Ionization)mentioning
confidence: 99%
“…Ketones in crude oil and coal tar were characterized by their molecular composition. Wang et al [29] further validate that the Girard-T derivatization followed by positive-ion ESI MS analysis is suitable for the analysis of ketones in a trace amount, but it has discrimination on high double-bond equivalent (DBE) species (DBE ≥ 9).…”
Section: Introductionmentioning
confidence: 98%
“…In recent years, a novel approach based on chemical derivatization followed by ESI high-resolution mass spectrometry has been used for the molecular characterization of ketones in fossil fuels [28][29][30]. The Girard-T reagent can be used to selectively create a positively charged quaternary ammonium moiety on carbonyls that can be accessed by ESI [31].…”
Section: Introductionmentioning
confidence: 99%